Cor Triatriatum with Mitral Valve Disease in Adults - Fuster-Siebert, M. (1982)
One 16-year-old boy with cor triatriatum and congenital mitral regurgitation and two women, 35- and 54-years-old, with cor triatriatum and rheumatic mitral stenosis are reported. The regurgitant mitral valve in the boy had three papillary muscles and short chordae tendineae. One of the patients with rheumatic mitral stenosis had a subtotal cor triatriatum with enlargement of the left atrial appendage and without asymmetry in the signs of pulmonary congestion. The mitral regurgitation facilitated the angiographic diagnosis of cor triatriatum. However, neither of the two patients associated with rheumatic mitral stenosis were correctly diagnosed preoperatively. All three patients were operated on with satisfactory results.